2007
DOI: 10.1152/ajpcell.00458.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia alters Ca2+ handling in rat cardiomyocytes by augmented Na+/Ca2+ exchange and ryanodine receptor activities in ischemia-reperfusion

Abstract: This study examined Ca(2+) handling mechanisms involved in cardioprotection induced by chronic intermittent hypoxia (CIH) against ischemia-reperfusion (I/R) injury. Adult male Sprague-Dawley rats were exposed to 10% inspired O(2) continuously for 6 h daily from 3, 7, and 14 days. In isolated perfused hearts subjected to I/R, CIH-induced cardioprotection was most significant in the 7-day group with less infarct size and lactate dehydrogenase release, compared with the normoxic group. The I/R-induced alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 50 publications
5
40
0
Order By: Relevance
“…These data suggest that the anti-calcium overload effect of CIHH might be one of the mechanisms for cardioprotection of CIHH in the developing rat. It has been shown that the cardioprotective effects of CIHH in the adult rat are related to the maintenance of calcium homeostasis via activation of PKC isoforms [34]. Similarly, we found that the anti-calcium overload effect of CIHH in developing rats was inhibited by the PKC inhibitor, suggesting that the activation of PKC contributes to the Ca 2+ homeostasis in CIHH cardioprotection.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These data suggest that the anti-calcium overload effect of CIHH might be one of the mechanisms for cardioprotection of CIHH in the developing rat. It has been shown that the cardioprotective effects of CIHH in the adult rat are related to the maintenance of calcium homeostasis via activation of PKC isoforms [34]. Similarly, we found that the anti-calcium overload effect of CIHH in developing rats was inhibited by the PKC inhibitor, suggesting that the activation of PKC contributes to the Ca 2+ homeostasis in CIHH cardioprotection.…”
Section: Discussionsupporting
confidence: 72%
“…It was reported that enhanced gene expression of NCX attenuates ischemic and hypoxic contractile dysfunction [39]. A previous study of the adult heart has shown that, although CIHH has little effect on the myocardial NCX1 protein level, CIHH maintains NCX activity during I/R [26,34]. In the present study, CIHH-treated developing rats displayed an increase in NCX1 protein levels with decreased [Ca 2+ ] i in myocardium during I/R, suggesting that the increase in the NCX protein expression contributes to the anti-calcium overload effects of CIHH.…”
Section: Discussionmentioning
confidence: 99%
“…C[Ca 2ϩ ]i transient amplitude was used as a measurement of SR Ca 2ϩ content (22,51,54). In the presence of caffeine, the elimination of Ca 2ϩ is mainly attributed to NCX.…”
Section: Methodsmentioning
confidence: 99%
“…I/R leads to decreased forward activity of NCX, or reversal of its function, with subsequent accumulation of [Ca 2ϩ ] i , prolongation of action potentials, and risk of arrhythmias (139,229). Based on measurements of Ca 2ϩ transients in cardiomyocytes, long-term IH preconditioning had no effect on baseline (preischemic) NCX activity or protein quantity; however, IH diminished ischemia-induced prolongation of Ca 2ϩ transients either induced by electric stimulation or by Ca 2ϩ release from the SR (262). Furthermore, it has been shown recently that NCX mRNA is increased following IH exposure in mice hearts (37).…”
Section: Circulatory Systemmentioning
confidence: 99%
“…Furthermore, it has been shown recently that NCX mRNA is increased following IH exposure in mice hearts (37). NCX activity was not influenced by IH when cells were exposed to PKC inhibitors, whereas PKA and CaMK inhibitors had no effect (262). Besides these preconditioning-related effects, NCX plays crucial role in IH-induced development of left ventricular dilation and systolic dysfunction (37).…”
Section: Circulatory Systemmentioning
confidence: 99%